The unique and joint contributions of various socialization agents to the acquisition of political knowledge among elementary school children in Israel. Issue 2 (3rd April 2019) - Hadar-Shoval, Dorit; Alon-Tirosh, Michal
ABSTRACT: The current study seeks to identify the socialization agents that contribute to the political knowledge of elementary school children in Israel. The study's underlying assumption is that understanding how young children acquire political knowledge is important because occurrences during early childhood have a major impact on socialization. The research considers the methodological difficulties involved in working with this age group and the perspectives associated with cultural structuring, according to which children are apolitical and therefore lack political knowledge or insights. The research examines political knowledge in the context of Israeli elections for the parliament and the prime minister and was conducted around a month prior to the elections. The results reveal that the dominant socialization agents contributing to children's political knowledge are parents, television and school. In addition, the study found that a combination of a number of socialization agents yields increased political knowledge.